POTRET KEHIDUPAN SOSIAL EKONOMI MASYARAKAT DI DESA KOTA LAMA KECAMATAN KAMPAR KIRI HULU KABUPATEN KAMPAR - Helen, Rafica Marta; ", Syafrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research was conducted in the village Kota Lama sub-district Kampar Kiri Hulu district Kampar. The purpose of this study was to analyze the socio-economic welfare of society in the village Kota Lama and topics focus of this research is how accessibility in the village Kota Lama. The sample in this study amounted to 7 people. The author uses qualitative descriptive method and the data were analyzed qualitatively. These research subjects are people who use public transport services and the local community. Sampling was done by purposive sampling technique. Instruments Data were observation, interviews and documentation. The results showed that the development is in the village Kota Lama a development that is still in the stage of traditional law of the five stages of development according to William Wilt Rostow. This can be seen by the facilities inadequate and is not available in Desa Kota Lama such as educational facilities, economic facilities (markets and cooperatives) as well as access roads were very bad and far from enough. Economic life of society Kota Lama fairly poor. community work Kota Lama as the rubber farmers are not able to meet the needs of every day. But people still tries to get his needs fulfilled effort made is to take other jobs in the forest looking for wood modang skins in the sun and then sold to penada. The economic situation and development is very alarming and the government makes public the village together to find ways to sustain their lives, every society collaborated in the development of infrastructure the building of access roads because of the village Kota Lama still preserve culture and one of is the culture gotong royong.Keywords: Rural Community, Development, Social, Economy